Analisis faktor yang berhubungan dengan status gizi dengan kejadian anemia pada ibu hamil - Yusuf Firmansyah; Wayan Aryawati; Dhiny Easter Yanti; Dessy Hermawan; Karbito Karbito (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: Nutritional status was one of the determinants of the health development, WHO predicts 40% of pregnant women worldwide suffer from anemia, the proportion of anemia in pregnant women in Indonesia is 48.9%, in Lampung Province is 37.1%, in West Coast District is 21 % and in Bengkunat Health Center by 18%. the proportion of anemia in pregnant women in Indonesia increased from 37.1% in 2013 to 48.9% in 2018.Purpose: To analyze factors related to the nutritional status of pregnant women based on measurements of Hb levels in the working area of Bengkunat Primary Health Care in Pesisir Barat District year 2022.Method: This type of research was quantitative with a cross-sectional design, a population of 515 pregnant women in the 1st and 2nd trimesters and a sample of 225 pregnant women using quota sampling technique, then analyzed by chi square and logistic regression.Results: The study found a varied and nutritionally balanced diet (p value=0.000 and OR=4.4), intake of foods rich in iron sources (p value=0.015 and OR=2.4), repeated pregnancies in a short time (p-value = 0.004 and OR = 3.1), education (p-value = 0.013), adherence to taking iron tablets (p-value = 0.000 and OR = 3.2) with the nutritional status of pregnant women. The variable most related to the nutritional status of pregnant women was adherence to taking iron tablets (OR 3.0), followed by a varied and nutritionally balanced diet (OR 2.7), repeated pregnancies in a short time (OR 2.2), and education with (OR 2.1) influence on the nutritional status of pregnant women.Conclusion: There is a relationship between the nutritional status of pregnant women based on the measurement of Hb levels. Pregnant women who do not adhere to taking iron tablets have a risk of experiencing anemia 3 times higher than pregnant women who adhere to taking iron tablets.Suggestion: to the UPTD head of the Bengkunat Health Center to create a nutritional literacy program for pregnant women, especially adherence to taking blood-boosting tablets, empowering husbands and families as supervisors for taking blood-boosting tablets and using reminders on personal cellphones to increase medication adherence, launching a fish-eating movement for pregnant women and competitions for counseling for cadres to deliver health nutrition messages on medication adherence in an effort to prevent anemia in pregnancy.Keywords: Nutritional Status; Anemia; Pregnant womenPendahuluan: Status gizi adalah salah satu faktor penentu keberhasilan pembangunan kesehatan, WHO memprediksi 40% wanita hamil di seluruh dunia menderita Anemia, proporsi anemia di Indonesia sebesar 48,9%, di Propinsi Lampung 29,1%, di Kabupaten Pesisir Barat sebesar 21% di UPTD Puskesmas Bengkunat sebesar 18%. Proporsi anemia pada ibu hamil di Indonesia meningkat dari 37,1% pada tahun 2013 menjadi 48,9% pada tahun 2018.Tujuan: Dianalisisnya faktor yang berhubungan dengan status gizi ibu hamil berdasarkan pengukuran kadar Hb di wilayah kerja UPTD Puskesmas Bengkunat Kabupaten Pesisir Barat Tahun 2022.Metode: Jenis penelitian kuantatif dengan rancangan potong lintang, populasi 515 ibu hamil pada trimester 1 dan 2 dan sampel 225 ibu hamil dengan kriteria inklusi dan ekslusi. Sampel diambil dengan teknik kuota sampling, lalu dianalisis dengan analisis bivariate dengan chi square dan multivariate dengan regresi logistik.Hasil: Didapatkan pola makan beragam dan bergizi seimbang (p value=0,000 dan OR=4,4), asupan makanan kaya sumber zat besi (p value=0,015 dan OR=2,4), kehamilan yang berulang dalam waktu singkat (p value=0,004 dan OR=3,1), pendidikan (p value=0,013), kepatuhan minum tablet tambah darah (p value=0,000 dan OR=3,2) dengan status gizi ibu hamil. Variabel yang paling berhubungan dengan status gizi ibu hamil adalah kepatuhan minum tablet tambah darah (OR 3,0), disusul oleh pola makan beragam dan bergizi seimbang (OR 2,7), Kehamilan yang berulang dalam waktu singkat (OR 2,2) dan pendidikan dengan (OR 2,1) berpengaruh pada status gizi ibu hamil. Simpulan: Terdapat hubungan status gizi ibu hamil berdasarkan pengukuran kadar Hb. Ibu hamil yang tidak patuh minum tablet tambah darah memiliki risiko mengalami anemia 3 kali lebih tinggi dibandingkan ibu hamil yang patuh minum obat tablet tambah darah.Saran: kepada kepala UPTD Puskesmas Bengkunat untuk membuat program literasi gizi ibu hamil khususnya kepatuhan minum tablet tambah darah, memberdayakan suami dan keluarga sebagai pengawas minum tablet tambah darah dan menggunakan alat bantu pengingat di ponsel pribadi untuk meningkatkan kepatuhan minum obat, mencanangkan gerakan makan ikan bagi ibu hamil dan lomba bagi penyuluhan bagi kader untuk menyampaikan pesan gizi kesehatan kepatuhan minum obat dalam upaya pencegahan anemia kehamilan.